PROGRAM PENGUNGKAPAN SUKARELA (PPS) PERPAJAKAN TAHUN 2022 - Suhendar, Endang; Setyorini, Christina Tri (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
The study aims to fill gaps in the study by doing a systematic library review to identify and analyze the factors affecting the tax voluntary disclosure program (PPS) in 2022. This study method is a systematic literature review by following the systematic literacy process consisting of the main stages of revving planning, recitation, and reporting. Based on the results of the selection, as many as 12 papers are used for this systematic literature search based on the inclusion and exclusion criteria. Extracted data were integrated to create survey questions presented for review purposes. The review literature review of all research published from the paper published from 2020-2022 states that the factors affecting voluntary disclosure programs (PPS) in 2022 were untargeted because of the covid-19 pandemic in 2020-2021 and resulted in tax duty not reporting as much as yearly. And this has turned Indonesia into an economic recession. The benefit of the voluntary disclosure program (PPS) in 2022 is increased tax compliance in reporting and following tax rules. Nevertheless, one of the flaws in the administration of this program is the lack of a taxpayer's misunderstanding of newly judged tax rules.